PENGARUH HARGA DAN PROMOSI ONLINE MELALUI INSTAGRAM TERHADAP KEPUTUSAN PEMBELIAN DENGAN MINAT BELI SEBAGAI VARIABEL INTERVENING PADA TOKO RIFKHASIRA DI SITUBONDO (Studi kasus mahasiswa Universitas Abdurachman Saleh Situbondo Angkatan 2018) - Sariyanti, Sariyanti; Tulhusnah, Lusiana; Soeliha, Siti (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Marketing is the beginning of a sale. In sales, performance is measured based on how many transactions were successfully closed and some value from the transaction. Judging from the timeframe, selling aims to get marketshare where products and prices become weapons in selling. The purpose of this study is to analyze and test the influence of Online Pricing and Promotion through Instagram on Purchasing decisions with Buying interest as an intervening variable in the Rifkhasira Store. The population in this study was students of Abdurachman Saleh Situbondo University class of 2018. The sampling technique uses random sampling techniques. This data analysis and testing uses the Structural Equation Model – Partial Least Square (PLS). Based on the hypothesis test of direct influence using the Smart PLS 3.0 application, the results of the study showed that Price has a significant positive effect on buying interest, Promotion has a significant positive effect on buying interest, Price has a positive but insignificant effect on purchasing decisions, Promotion has a significant positive effect on purchasing decisions, buying interest has a significant positive effect on purchasing decisions, price has a significant effect on purchasing decisions. to the purchase decision through buying interest, promotion positively affects the purchase decision through buying interest.